Keterlibatan Masyarakat Desa Benteng Tado-Manggarai NTT Dalam Pemilu Bagi Kesejahteraan Sosio-Ekonomi Menurut Filsafat Politik Armada Riyanto - Mathias Jebaru Adon (Universitas Islam Darul Ulum Lamongan, 2021)
The focus of this study aims to explore the understanding of the people of Benteng Tado towards political democracy in Manggarai-Flores NTT. In particular, their involvement in the election of legislative candidates so that it can provide benefits for the welfare of socio-economic life. The methodology used in this study is a quantitative method. Data was collected through a questionnaire distributed via a google form. This research was carried out through critical analysis according to Armada Riyanto's political philosophy. Armada Riyanto's concept of politics as the governance of everyday life becomes the theoretical foundation in analyzing the involvement of the people of Benteng Tado in elections and their impact on socio-economic life. This study found that the understanding of the people of the Benteng Tado towards democracy was still limited to their involvement in the general election. In other words, the people of Bentang Tado do not understand that politics is a means to improve social welfare, especially post-election.